Changes in Morphometric Traits of Ground Beetles Along Urbanization Gradients. Issue 1 (11th January 2020) - Papp, Dalma; Mizser, Szabolcs; Nagy, Leila; Vidic, Andreas; Simon, Edina; Tóthmérész, Béla
Abstract: Urbanization has a significant impact on abiotic and biotic factors in nature. We examined the morphometric characters of four carabid species ( Abax parallelepipedus, Carabus scheidleri, Carabus violaceus, and Pterostichus oblongopunctatus ) along urbanization gradients in and around the cities of Vienna (Austria) and Debrecen (Hungary). We found significant differences among urban, suburban, and rural areas in the parameters of antennomers, the maxillary palpus, the labial palpus, and the length of the tibia and the elytra of the carabids studied. We also found significant differences between males and females based on the parameters of antennomers, the maxillary palpus, the labial palpus, the femur, and the elytra. An interaction between urbanization and sex was found in the case of antennomers, the maxillary palpus, the labial palpus, the femur, and the elytra. Our findings suggested that in the cases of species from Carabini tribus the parameters of antennomers, the maxillary palpus, and the elytra could be useful for assessing the effects of urbanization because these morphometric characters responded sensitively to the environmental stress, whereas the most useful parameters are those of antennomers and the tibia for the species of Pterostichini tribus. Our findings also revealed that females are more sensitive to environmental stress than males.